Mechanical instability induces osteoclast differentiation independent of the presence of a fibrous tissue interface and osteocyte apoptosis in a rat model for aseptic loosening. (2nd January 2020) - Madsen, Rune Vinther; Nam, Denis; Schilcher, Jörg; Dvorzhinskiy, Aleksey; Sutherland, James P; Bostrom, F Mathias; Fahlgren, Anna
Abstract : Background and purpose — Insufficient initial fixation or early micromotion of an implant is associated with a thin layer of fibrous tissue at the peri-implant interface. It is unknown if bone loss is induced by the fibrous tissue interface acting as an active biological membrane, or as a membrane that will produce supraphysiologic fluid flow conditions during gait, which activates the mechanosensitive osteocytes to mediate osteoclast differentiation. We investigated whether mechanically induced osteolysis is dependent on the fibrous tissue interface as a biologically active scaffold, or if it merely acts as a conduit for fluid flow, affecting the mechanosensitive osteocytes in the peri-prosthetic bone. Methods — Using a rat model of mechanically instability-induced aseptic loosening, we assessed whether the induction of osteoclast differentiation was dependent on the presence of a peri-implant fibrous interface. We analyzed the amount of osteoclast differentiation, osteocyte apoptosis, pro-resorptive cytokine expression and bone loss using immunohistochemistry, mRNA expression and micro-CT. Results — Osteoclast differentiation and bone loss were induced by mechanical instability but were not affected by the presence of the fibrous tissue membrane or associated with osteocyte apoptosis. There was no increased mRNA expression of any of the cytokines in the fibrous tissue membrane compared with the peri-implant bone. Interpretation — Our data show that the fibrous tissue membrane in the interface plays a minor role in inducing bone loss. This indicates that the peri-implant bone adjacent to loose bone implants might play an important role for osteoclast differentiation.